Research on the impact of water-saving technologies on the agricultural production efficiency of high-quality farmers------taking Jiangxi province and Guangdong province in China as examples - Lei, Xiankai; Yang, Dongmei (Frontiers in Environmental Science, 2024)
Based on the survey data of 1707 high-quality farmers in Guangdong and Jiangxi provinces in China, this article uses the DEA-tobit model and propensity score matching method to explore the impact of water-saving technology adoption on agricultural production efficiency from a micro perspective. The research results show that the adoption of water-saving technology by high-quality farmers can significantly improve agricultural production efficiency. By comparing the results with the baseline regression using propensity score matching method, the study findings are found to be robust.The mechanism and results of the study indicate that agricultural subsidy policies play a regulatory role between water-saving technology adoption and the agricultural production efficiency of high-quality farmers. Further analysis reveals that the impact of water-saving technology on the production efficiency of different types of high-quality farmers varies. Specifically, water-saving technology has a greater impact on the production efficiency of farmer cooperatives and agricultural enterprises compared to large-scale farming households and family farms. Therefore, policy recommendations are proposed to improve the water-saving agricultural technology system, among other aspects.